Partial splenectomy in cystic fibrosis patients with hypersplenism. Issue 2 (1st February 2003) - Thalhammer, G H; Eber, E; Uranüs, S; Pfeifer, J; Zach, M S
Abstract : We report three cystic fibrosis (CF) patients with hypersplenism who underwent partial splenectomy. The postoperative course was uneventful in two patients; one patient developed a complication necessitating resection of the rest of the spleen. Haematological parameters improved and oesophageal varices regressed in all patients. On follow up, one patient showed a normal spleen, the other a normally functioning accessory spleen; the third patient again developed splenomegaly with hypersplenism. Partial splenectomy is a promising therapeutic option for CF patients with hypersplenism.